PADIATAPA DAN PERHUTANAN SOSIAL: Studi Kasus Pengusulan Hutan Desa di Kabupaten Sinjai: Studi Kasus Pengusulan Hutan Desa di Kabupaten Sinjai - Mas'ud, Emban Ibnurusyd; Ikhsan, Muh.; A. Samsu, Andi Khairil; Nasir, Anugrahandini (Jurnal Eboni, 2024)
The implementation of FPIC for many program developments, which aligns with the common global issue of Sustainable Development Goals, has become a spotlight nowadays. This research explores how the FPIC works within a formal community forestry scheme initiation in Indonesia. With participant observation as the main hypothetical view and triangulating with the community members’ view both in elite structure as well as regular members, the article finds a glorified claim of this concept had been conducted rather than to meet its core value on initiating community forestry scheme in Sinjai Village.